Socio-economic vulnerability to natural disasters in Mexico : rural poor, trade and public response - Saldaña-Zorrilla, Sergio O. (CEPAL MexicoMX, 2007)
Assesses public response to natural disasters in Mexico, including risk sharing and loss-transfer instruments. Concludes with a set of policy suggestions to the public sector in order to maximize benefits from the existing governmental programmes for adaptation to the increasing natural hazard exposure of the the country.